INKLUSIVITAS PARTISIPASI POLITIK LOKAL: ANALISIS KETERLIBATAN KELOMPOK MARGINAL DALAM PENYUSUNAN PERATURAN DAERAH DI KOTA MATARAM - Ayatullah Hadi; Iwan Tanjung Sutarna; Ajai Saputra; Hidayatullah, Hidayatullah (Nusantara Hasana Journal, 2025)
This study aims to analyze the involvement of marginalized groups in the formulation of regional regulations (Perda) in Mataram City within the framework of inclusive local political participation. This study uses a qualitative method with a Systematic Literature Review (SLR) approach to scientific articles published in the last five years (2021–2025) and available in the Dimensions and Scopus databases. Only literature that meets the eligibility criteria—including topic relevance, journal reputation, and full-text availability—is systematically analyzed. The results of the study show that the participation of marginalized groups, such as female heads of households, people with disabilities, and indigenous communities, is still hampered by structural and cultural factors. Existing participatory mechanisms are symbolic and not substantively inclusive. Although digital technology offers the potential to expand participation, its implementation still faces challenges in terms of social justice and cultural sensitivity. This study recommends the need to integrate the principles of intersectionality, social justice, and participatory evaluation in the formulation of Perda. This study contributes to filling the literature gap on inclusive local political participation and offers a new direction for regional policies that are more transformative and responsive to the needs of vulnerable groups.